2012
DOI: 10.1111/hae.12002
|View full text |Cite
|
Sign up to set email alerts
|

Dental health and oral health‐related quality of life in children with congenital bleeding disorders

Abstract: Summary. The purpose of this study was to investigate the dental and some other aspects of oral health status of young patients with congenital bleeding disorders (CBD) and the impact of these on their quality of life (OHR-QoL) compared with controls. DMFS-dmfs (Decayed, Missed, Filled Tooth surfaces in permanent and primary teeth) scores, Simplified oral hygiene index, occurance of hypoplasia of first permanent molars, Temporomandibular joint dysfunction and occlusion of 46 CBD patients at the age range of 2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(69 citation statements)
references
References 25 publications
6
58
2
3
Order By: Relevance
“…Similar to other studies, majority of these patients attended Specialist Dental Clinics and had regular, scheduled dental appointments [5,18,19]. Similar to other studies, majority of these patients attended Specialist Dental Clinics and had regular, scheduled dental appointments [5,18,19].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similar to other studies, majority of these patients attended Specialist Dental Clinics and had regular, scheduled dental appointments [5,18,19]. Similar to other studies, majority of these patients attended Specialist Dental Clinics and had regular, scheduled dental appointments [5,18,19].…”
Section: Discussionsupporting
confidence: 87%
“…The multidisciplinary approach was also reported in other studies that found similar or lower caries experience among haemophilia patients as compared to healthy controls [5,18,19]. The multidisciplinary approach was also reported in other studies that found similar or lower caries experience among haemophilia patients as compared to healthy controls [5,18,19].…”
Section: Discussionsupporting
confidence: 69%
“…An Iranian study showed that children with a congenital bleeding disorder (aged 2-15 years) have a better dental health situation in primary dentition and a similar oral health-related QoL, assessed with the OHR-QoL, compared to children without congenital bleeding disorders [90].…”
Section: Results In Adult Hemophilia Patientsmentioning
confidence: 99%
“…As a result, people with haemophilia can bleed for longer than normal, and some may experience bleeding into joints, muscles, or other parts of their bodies that can lead to joint damage and disability. This disorder, especially in its severe forms, has been associated with mortality and morbidity (Salem and Eshghi 2013). Prophylactic therapy, which involves regular factor replacement (at least three times per week or daily), is of critical importance (Manco-Johnson et al 2007).…”
Section: Methodsmentioning
confidence: 99%